The Newspaper "Albayrak" - the Founder of the Denial Thesis: "Eastern Provinces Will Not Become Armenia" (1919-1920) - Mirzoyan, Elina (History and Culture, 2022)
The newspaper "Albayrak" was the official publication of the "Union and Progress" committee (CUP) in Erzrum, and in the first period served to promote Turkism. It was published in 1913, after an interruption it was republished in 1919. The most influential period was 1919-1920, when it was a propaganda tool of the Ittihat policy against the Armenians and the Armenian Question. The newspaper was republished in response to the Mudros Armistice, laying the foundation for a large-scale thesis - "Eastern provinces will not become Armenia", which subsequently changes as a response to the Treaty of Alexandropol: "Eastern states are the homeland of the Turks." The newspaper sowed hatred towards the Armenians, allegedly showing the world the rebuttal fact that in the East it is not the Turks who kill the Armenians, but the Armenians who kill the Turks. Criticism of those countries that supported the Armenian Question was the unshakable position of the newspaper.